Relative responsiveness of condition specific and generic health status measures in juvenile idiopathic arthritis. Issue 2 (12th January 2005) - Moretti, C; Viola, S; Pistorio, A; Magni-Manzoni, S; Ruperto, N; Martini, A; Ravelli, A
Abstract : Objectives: To compare the relative responsiveness of condition specific measures with that of a generic health status instrument for outcome assessment of intra-articular corticosteroid (IAC) injection in patients with juvenile idiopathic arthritis (JIA). Methods: We examined 44 consecutive patients with oligoarticular JIA before an IAC injection and after 6 months. Condition specific measures included physician's and parent's global assessments, the Childhood Health Assessment Questionnaire (CHAQ), the articular indices, and laboratory indicators of systemic inflammation. The generic health status instrument was the Child Health Questionnaire (CHQ), which was divided into two parts: the physical score (PhS) and the psychosocial score (PsS). Responsiveness statistics were the standardised response mean, the effect size, and Guyatt's method. The discriminative ability of the clinical measures in distinguishing improved from non-improved patients was evaluated with the correlation and the receiver operating characteristic methods, using the physician's and the parent's judgements of the treatment outcome as external criteria. Results: All responsiveness statistics and discriminative ability assessments consistently ranked the physician's global assessment of the disease activity as the most responsive measure. The CHQ-PhS revealed superior ability in detecting baseline versus 6 month change compared with the CHAQ and the CHQ-PsS; both summary scales of the CHQ revealed better discriminative ability than the CHAQ. Conclusions: The physician's global assessment of the disease activity proved the most responsive outcome measure in our patients with JIA. The relative evaluative properties of the generic health status instrument and the CHAQ should be further investigated.